Indicaxanthin from Cactus Pear Fruit Exerts Anti-Inflammatory Effects in Carrageenin-Induced Rat Pleurisy. Issue 2 (4th December 2013) - Allegra, Mario; Ianaro, Angela; Tersigni, Mariaroberta; Panza, Elisabetta; Tesoriere, Luisa; Livrea, Maria Antonia
Abstract: Nutritional research has shifted recently from alleviating nutrient deficiencies to chronic disease prevention. We investigated the activity of indicaxanthin, a bioavailable phytochemical of the betalain class from the edible fruit of Opuntia ficus-indica (L. Miller) in a rat model of acute inflammation. Rat pleurisy was achieved by injection of 0.2 mL of λ-carrageenin in the pleural cavity, and rats were killed 4, 24, and 48 h later; exudates were collected to analyze inflammatory parameters, such as nitric oxide (NO), prostaglandin E2 (PGE2 ), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α); cells recruited in pleura were analyzed for cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS) expression, and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) activation. Indicaxanthin (0.5, 1, or 2 μ mol/kg), given orally before carrageenin, time- and dose-dependently, reduced the exudate volume (up to 70%) and the number of leukocytes recruited in the pleural cavity (up to 95%) at 24 h. Pretreatment with indicaxanthin at 2 μ mol/kg inhibited the carrageenin-induced release of PGE2 (91.4%), NO (67.7%), IL-1β (53.6%), and TNF-α (71.1%), and caused a decrease of IL-1 β (34.5%), TNF -α (81.6%), iNOS (75.2%), and COX2 (87.7%) mRNA, as well as iNOS (71.9%) and COX-2 (65.9%) protein expression, in the recruited leukocytes. Indicaxanthin inhibited time- and dose- dependently the activation of NF-κB, a key transcription factor in the whole inflammatory cascade. A pharmacokinetic study with a single 2 μ mol/kg oral administration showed a maximum 0.22 ± 0.02 μ mol/L ( n = 15) plasma concentration of indicaxanthin, with a half-life of 1.15 ± 0.11 h. When considering the high bioavailability of indicaxanthin in humans, our findings suggest that this dietary pigment has the potential to improve health and prevent inflammation-based disorders.